Indicators of Regional Innovation Clusters' Effectiveness in the Higher Education System - Iryna Lysenko; Serhii Stepenko; Hanna Dyvnych (MDPI AG, 2020)
Under globalization conditions, the main priority of the state education policy in many countries of the world is to ensure higher education quality. This is possible through close and efficient cooperation between the state, higher education institutions, future specialists, employers and innovative structures (clusters). This study focuses on the development of indicators that can comprehensively assess the effectiveness of regional innovation clusters in the higher education system. The main attention is given to the analysis of innovations, business, education development and competitiveness, as indicators of the effectiveness of regional innovation clusters in the higher education system. The following methods have been used within the research: content analysis, statistical, correlation and regression analysis, econometric modeling and the graphical method. As a result of the research, indicators of the effectiveness of regional innovation clusters have been identified and the impact of these indicators on the higher education system has been evaluated. The authors have shown that there is a close relationship between the level of development of regional innovation clusters, indicators of business and innovations development, and the level of competitiveness. The direct impact of those on the higher education system has been established and confirmed by the provided calculations.